Case 3840: Proterochersis robusta Fraas, 1913 (Testudinata, Proterochersidae): proposed conservation of the generic and specific name by conditional suppression of Chelytherium obscurum Meyer, 1863 - Szczygielski, Tomasz (Bulletin of Zoological Nomenclature)
Noticed in BZN 78 (30 Apr 2021): 2.